B-spline Parameterization Based Flight Trajectory Optimization - Teixeira, Rose Avelino Correia (2022)
Achieving the first heavier-than-air flight during the 20th century was certainly a great landmark in human history. However, flight itself generally is not the final objective. To perform the desired mission effectively, it is necessary to determine the path to follow according to the objective, for instance minimizing the elapsed time, the path length, etc. How do we deal with such problems? Which are the techniques to solve them? Trajectory Optimization is the subject that deals with such problems, and the object of study of the present dissertation. I propose to study the use of B-spline Parameterization for Flight Trajectory Optimization. A Python code was developed to implement the proposed method, revealing promising results for all three presented examples, proving the robustness and versatility of the proposed method. Future studies should explore different types of missions, including spatial trajectories, and various sets of waypoints. The study and implementation of the control to stimulate the desired flying device to follow the determined optimal trajectory would also constitute an interesting exercise.